A Greater Improvement of Intrahepatic Fat Contents after 6 Months of Lifestyle Intervention Is Related to a Better Oxidative Stress and Inflammatory Status in Non-Alcoholic Fatty Liver Disease - Margalida Monserrat-Mesquida; Magdalena Quetglas-Llabrés; Cristina Bouzas; Sofía Montemayor; Catalina M. Mascaró; Miguel Casares; Isabel Llompart; José M. Gámez; Silvia Tejada; J. Alfredo Martínez; Josep A. Tur; Antoni Sureda (MDPI AG, 2022)
Non-alcoholic fatty liver disease (NAFLD) is a disorder characterized by the excessive accumulation of lipids in the liver parenchyma. To date, there is no effective pharmacological treatment against NAFLD. Objective: To assess the relationship between the improvement of the intrahepatic fat content (IFC) in patients with NAFLD and metabolic syndrome and biomarkers of oxidative stress and inflammation after 6 months of lifestyle intervention. Patients diagnosed with NAFLD (n = 60 adults; 40-60 years old) residing in the Balearic Islands, Spain, were distributed in tertiles attending the improvement of IFC calculated by magnetic resonance imaging (MRI). Anthropometrics, blood pressure, maximal oxygen uptake, and pro/antioxidant and inflammatory biomarkers were determined in plasma before and after the lifestyle intervention. The improvement in IFC levels was higher in tertile 3 with respect to tertiles 2 and 1. The greatest improvement in IFC is related to cardiorespiratory fitness and adherence to the Mediterranean diet (ADM). Higher reductions in weight, body mass index (BMI), and alanine aminotransferase (ALT) were observed in tertile 3 with respect to tertile 1 after 6 months of intervention. The improvement in catalase, irisin, and cytokeratin 18 plasma levels were higher in tertile 3, whereas no differences were observed in superoxide dismutase activity. Malondialdehyde and protein carbonyl levels, as biomarkers of oxidative damage, remained unchanged in all groups. The present data show that the reduction of IFC is associated with an improvement in pro/antioxidant and pro-inflammatory status and a better cardiorespiratory fitness in NAFLD patients.